PENGARUH DISCOUNT, BONUS PACK, DAN IN- STORE DISPLAY TERHADAP IMPULSE BUYING PRODUK OBAT NYAMUK HIT di PAMELLA SWALAYAN YOGYAKARTA - Mohamad Haironi (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this research was to examine the influence of Discount, Bonus pack, and In-store Display onImpulse buying of HIT mosquito repellent products at Pamella Swalayan Yogyakarta. This research wasquantitative causative research. The population in this study is were consumers who made purchases of HITin Pamella Swalayan Yogyakarta, with a sample of consumers who bought HIT Products in PamellaSwalayan Yogyakarta, amounting to 100 respondents. Data collection was held directly by using aquestionnaire. While the tools of analysis used was multiple regression with SPSS program version 16.0.The results showed that the Discount and Bonus pack variables have significantly influence to Impulsebuying of HIT mosquito repellent products in Pamella Swalayan Yogyakarta, while In-store Display has nosignificant influence to Impulse buying of HIT mosquito repellent product in Pamella Swalayan Yogyakarta.